Risks and farmers' behavior change towards water conservation: a study in the Southeast of Iran - Pouria Ataei; Hamid Karimi; Zeynab Hallaj; Afshin Mottaghi Dastenaei (Water Supply, 2024)
Frequent droughts in Iran have influenced farmers' social and economic lives and have entailed extensive negative consequences. This research aimed to study the process by which farmers adopt water conservation behavior and explore the intervention of perceived risks and risk attitude. This survey was conducted among farmers in the Sistan region in the southeast of Iran (N = 6,000). A sample of 361 farmers was selected by multistage cluster randomization. The research instrument was a researcher-made questionnaire whose reliability was checked by Cronbach's alpha and composite reliability in a pilot study and whose content validity was confirmed by a panel of agricultural sociologists. The data were analyzed using mean, percentage, and structural equation modeling in the SPSSwin26 and AMOS24 software suites. The results reveal that perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, and cues to action influence farmers' water conservation behavior positively and significantly. Also, most components of the health belief model are influenced by farmers' perceived risks and risk attitude. It can be concluded that it is imperative to focus on socio-psychological components to promote water conservation behavior and use water scarcity-coping strategies in Iran. HIGHLIGHTS Frequent droughts in Iran have influenced farmers' social and economic lives.; Most components of health belief model are influenced by farmers' perceived risks and risk attitude.; It is imperative to focus on socio-psychological components.;